Study of the Utilization of Medicinal Plants by Traditional Healer of the Tolaki Ethnic Tribe, Southeast Sulawesi, Indonesia - Saputra Tahoangako, Sarmadhan; Santosa, Djoko; Fakhrudin, Nanang (Ethnobotany Research and Applications, 2024)
Background: Plants are potential sources for drug discovery from natural resources. Indonesia, with its thousands of islands, harbors vast plant biodiversity. To identify promising plants for medication, an ethnomedicine study of medicinal plants was conducted in the Southeast Sulawesi Province of Indonesia. This study aimed to collect information on traditional medicinal plant usage. Methods: The identity of plants, parts of plants used for medication, preparation methods, and dosages were systematically documented through snowball sampling, involving interviews with traditional local healers (mbu'uwai) utilizing a comprehensive questionnaire covering disease types, plant species, preparation techniques, and dosing regimens. Data were analyzed both qualitatively and quantitatively, employing the Informant Consensus Factor (ICF) and Fidelity Level (FL) values. Results: The study revealed that 91 plant species from 44 families were utilized by healers. The most common diseases treated with medicinal plants are related to the eyes (0.97), osteoarticular system (0.96), digestive system (0.95), metabolic system (0.95), and cardiovascular system (0.95). Prominent medicinal plants include Andrographis paniculata (Burm.f.) Nees (100%), Chromolaena odorata L. (100%), Curcuma longa L. (100%), Orthosiphon aristatus Blume (100%), and Phaleria macrocarpa (Scheff.) Boerl. (100%). Leaves are the most commonly used plant part in traditional preparations, with boiling with water being the preferred method. Conclusions: This study demonstrates the persistent utilization of plants for medicinal purposes within the Tolaki ethnic tribe, highlighting several species with potential as prospective drug candidates. Notably, 91 species of medicinal plants are harnessed through boiling to address prevalent ailments. Keywords: Ethnopharmacology; Drug discovery; Informant Consensus Factor; Fidelity Level